A study on carbon emissions in the Yellow River Basin of China based on an unbiased prediction model - Guo, Weidong (Frontiers in Ecology and Evolution, 2025)
The birthplace of the Chinese country is the Yellow River Basin, which is related to ecological security and economic development. Studying the Yellow River Basin’s carbon emissions problems can support sustainable development, ecological preservation, and high-quality development. It can also give a scientific foundation for regional green and low-carbon transformation. Based on the data characteristics of carbon emissions in nine provinces in the Yellow River Basin, this paper selects a new unbiased, non-homogeneous grey prediction model (UNGM(1,1)) to analyze and predict whether the nine provinces in the Yellow River Basin will be able to reach the carbon peak by 2030. Through research, it was found that three of the nine provinces in the Yellow River Basin will peak in carbon emissions by 2030, namely Qinghai, Henan, and Sichuan. It will be unattainable for the remaining six provinces—Gansu, Ningxia, Inner Mongolia, Shanxi, Shaanxi, and Shandong—to reach the carbon peak by 2030. The findings of this study offer valuable reference for analyzing carbon emissions in the Yellow River Basin, formulating differentiated emission reduction policies, optimizing resource allocation, and precise implementation of dual carbon goals.